Therapeutic effect of high-dose green tea extract on weight reduction: A randomized, double-blind, placebo-controlled clinical trial - Chen, I-Ju; Liu, Chia-Yu; Chiu, Jung-Peng; Hsu, Chung-Hua (Clinical nutrition (Edinburgh, Scotland), 2016)
To examine the effect and safety of high-dose green tea extract (Epigallocatechin gallate, EGCG) at a daily dosage of 856.8 mg on weight reduction and changes of lipid profile and obesity-related hormone peptides in women with central obesity. We conducted a randomized, double-blind trial registered under ClinicalTrials.gov Identifier no. NCT02147041. A total of 115 women with central obesity were screened at our clinic. 102 of them with a body mass index (BMI) ≥ 27 kg/m2 and a waist circumference (WC) ≥ 80 cm were eligible for the study. These women were randomly assigned to either a high-dose green tea group or placebo group. The total treatment time was 12 weeks. The main outcome measures were anthropometric measurements, lipid profiles, and obesity related hormone peptides including leptin, adiponectin, ghrelin, and insulin. Significant weight loss, from 76.8 ± 11.3 kg to 75.7 ± 11.5 kg (p = 0.025), as well as decreases in BMI (p = 0.018) and waist circumference (p = 0.023) were observed in the treatment group after 12 weeks of high-dose EGCG treatment. This study also demonstrated a consistent trend of decreased total cholesterol, reaching 5.33%, and decreased LDL plasma levels. There was good tolerance of the treatment among subjects without any side effects or adverse events. Significantly lower ghrelin levels and elevated adiponectin levels were detected in the study group than in the placebo group. 12 weeks of treatment with high-dose green tea extract resulted in significant weight loss, reduced waist circumference, and a consistent decrease in total cholesterol and LDL plasma levels without any side effects or adverse effects in women with central obesity. The antiobestic mechanism of high-dose green tea extract might be associated in part with ghrelin secretion inhibition, leading to increased adiponectin levels. •High-dosage EGCG treatment can significantly reduce body weight in women with central obesity.•High-dosage EGCG treatment has good tolerance among subjects without any side effect or adverse effect.•The mechanism of high-dose EGCG in obesity might be through decreasing the secretion of ghrelin and lead to increase of adiponectin level.